Positive pole piece, electrochemical device comprising positive pole piece and electric device comprising positive pole piece

By regulating the particle size distribution and manganese content of LMFP agglomerates and nano-sized particle size particles, a positive electrode sheet with excellent fast charging performance and energy density was designed, which solved the shortcomings of traditional LFP and LMFP materials in terms of energy density and fast charging performance, and achieved synchronous improvement.

CN119627045AActive Publication Date: 2025-03-14CALB GROUP CO LTD

Patent Information

Application Number
CN202411800900.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-03-14
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

Traditional lithium iron phosphate (LFP) positive electrode materials have limitations in terms of energy density, and the fast charging performance of lithium iron phosphate (LMFP) materials is poor, requiring smaller particle sizes to improve electron conductivity, but this will lead to serious side reactions of the electrolyte, limiting the increase in energy density.

Method used

By regulating the particle size distribution of LMFP agglomerates and LMFP/LFP nanoscale particle size particles and the manganese content of the material, a positive electrode sheet with excellent fast charging performance and energy density was designed. The positive electrode sheet includes LMFP agglomerates with a particle size of 4 to 20 μm and LMFP/LFP nano-sized particle size particles with a particle size of 200 to 600 nm. The molar percentage content relationship of manganese element satisfies a specific range.

Benefits of technology

The synchronous improvement of the fast charging performance and energy density of the LMFP positive electrode sheet is achieved, and the problems of the energy density limitations of traditional LFP materials and the insufficient fast charging performance of LMFP materials are overcome.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627045A_ABST
    Figure CN119627045A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemistry, and particularly discloses a positive pole piece, an electrochemical device comprising the positive pole piece and an electric device. The positive pole piece comprises a first active material with a particle size of 4-20 [mu] m and a second active material with a particle size of 200-600 nm, the first active material comprises lithium manganese iron phosphate with the manganese content of m%, the second active material comprises lithium manganese iron phosphate and / or lithium iron phosphate with the manganese content of n%, and m and n meet the condition that m-n is larger than or equal to 15 and smaller than or equal to 85. According to the invention, by controlling the particle size distribution in the positive electrode active material and the manganese content relationship, the electrochemical device containing the positive electrode plate has excellent fast charging performance and energy density.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is CN118867136A (filing date is September 19, 2024, application number is

[0002] 202411305169.8. Divisional application for the invention entitled "A positive electrode sheet and an electrochemical device and an electrical device comprising the same". Technical Field

[0003] The present invention relates to the field of electrochemical technology, and in particular to a positive electrode sheet and an electrochemical device and an electrical device containing the same. Background Art

[0004] In recent years, with the rapid development of electric vehicles and energy storage systems, the demand for high-performance and high-safety power battery materials has become increasingly urgent. Lithium iron phosphate (LFP) cathode materials have received extensive attention and application due to their high safety, low cost, and long cycle life. However, traditional LFP materials have certain limitations in energy density. In order to overcome these limitations of traditional LFP materials, lithium manganese iron phosphate (LMFP) has high voltage and high energy density compared to lithium iron phosphate, and has become a highly regarded alternative.

[0005] Compared with LFP, LMFP has a lower diffusion coefficient and poorer fast charging performance. Therefore, for LMFP, a smaller particle size is required to reduce the diffusion path of lithium ions inside the positive electrode active material particles, so as to efficiently deintercalate and help improve electronic conductivity, thereby improving fast charging performance. However, when the LMFP particle size is small, there are too many reaction surfaces with the electrolyte, resulting in serious side reactions of the electrolyte, and for LMFP particles with small particle size, the amount of binder used needs to be increased, resulting in a decrease in the battery surface density, which limits the increase in energy density.

[0006] It has been reported in the prior art that the use of LMFP agglomerates containing multiple small-size primary particles can reduce the amount of binder used and increase energy density. However, the use of LMFP agglomerates limits the increase in the compaction density of the pole piece. During the high compaction process, the material may be broken and the electrochemical performance may deteriorate. In addition, agglomerates will also cause the bulk phase transmission capacity of the material to deteriorate, and the kinetic performance, especially the fast charging performance, will decrease.

[0007] Therefore, it is necessary to develop a positive electrode sheet that has both good fast charging performance and energy density. Summary of the invention

[0008] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a positive electrode plate and an electrochemical device and an electrical device containing the same. The positive electrode plate adopts the LMFP material system, and the particle size distribution of LMFP agglomerates and LMFP / LFP nano-particles, as well as the manganese content of the material are adjusted to make the positive electrode plate have both excellent fast charging performance and energy density.

[0009] To achieve the above object, in a first aspect of the present invention, the present invention provides a positive electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material, the positive electrode active material comprising a first active material having a particle size of 4 to 20 μm and a second active material having a particle size of 200 to 600 nm;

[0010] The first active material includes lithium manganese iron phosphate (LMFP), and the molar percentage of manganese in the first active material is m%, calculated based on the total molar number of metal elements other than lithium in the first active material;

[0011] The second active material comprises lithium iron manganese phosphate and / or lithium iron phosphate (LFP), and the molar percentage of manganese in the second active material is n% based on the total molar number of metal elements other than lithium in the second active material;

[0012] The m and the n satisfy the following relationship: 15≤mn≤85.

[0013] As a preferred embodiment of the present invention, the m and the n satisfy the following relationship: 40≤mn≤70.

[0014] As a preferred embodiment of the present invention, the m and the n satisfy the following relationship: 0.10≤n / m≤0.85.

[0015] As a further preferred embodiment of the present invention, the m and the n satisfy the following relationship: 0.18≤n / m≤0.45.

[0016] As a preferred embodiment of the present invention, the m% is 70 to 95%.

[0017] As a preferred embodiment of the present invention, the n% is 0 to 60%.

[0018] As a preferred embodiment of the present invention, the first active material includes secondary particles formed of primary particles, and the diameter of the primary particles is 20 to 130 nm.

[0019] As a preferred embodiment of the present invention, the molar ratio of manganese element to iron element (Mn / Fe) in the positive electrode active material is 1-4.

[0020] As a preferred embodiment of the present invention, the positive electrode sheet satisfies the following relationship: 5≤(a×b) / c≤60;

[0021] Said a is the value of mn;

[0022] b is the molar ratio of manganese to iron in the positive electrode active material;

[0023] The c is the peak intensity ratio of the diffraction peaks of the (101) crystal plane and the (020) crystal plane in the XRD spectrum of the positive electrode plate.

[0024] As a preferred embodiment of the present invention, the range of c is 0.75 to 1.13. In a second aspect of the present invention, the present invention provides an electrochemical device, comprising the above-mentioned positive electrode sheet.

[0025] In a third aspect of the present invention, the present invention provides an electrical device comprising the electrochemical device described above.

[0026] The beneficial effects of the present invention are:

[0027] The present invention provides a positive electrode sheet, an electrochemical device and an electric device comprising the positive electrode sheet. The positive electrode sheet of the present invention mainly adopts the LMFP material system, and by controlling the particle size distribution of LMFP / LFP agglomerates and nano-sized particles in the positive electrode active material, and the manganese content relationship of LMFP / LFP, the positive electrode sheet has both excellent fast charging performance and energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a SEM image of the positive electrode active material of Example 1 at 5K rate.

[0029] Figure 2 This is a SEM image of the positive electrode active material of Example 19 at a rate of 10K.

[0030] Figure 3 This is the XRD pattern of the positive electrode sheet prepared in Example 1.

[0031] Figure 4 This is the XRD pattern of the positive electrode sheet prepared in Example 19. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0034] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0035] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0036] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0037] An embodiment of the present invention provides a positive electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material, the positive electrode active material comprising a first active material having a particle size of 4 to 20 μm and a second active material having a particle size of 200 to 600 nm;

[0038] The first active material includes lithium manganese iron phosphate (LMFP), and the molar percentage of manganese in the first active material is m%, calculated based on the total molar number of metal elements other than lithium in the first active material;

[0039] The second active material comprises lithium iron manganese phosphate and / or lithium iron phosphate (LFP), and the molar percentage of manganese in the second active material is n% based on the total molar number of metal elements other than lithium in the second active material;

[0040] The m and the n satisfy the following relationship: 15≤mn≤85.

[0041] The present invention has found that by using LMFP agglomerates with high manganese content in combination with LMFP nanoparticles with low manganese content and / or manganese-free LFP nanoparticles, the fast charging performance and energy density of the positive electrode plate of the lithium manganese iron phosphate system can be improved simultaneously.

[0042] In the present invention, the positive electrode active material includes a first active material with a particle size of 4 to 20 μm and a second active material with a particle size of 200 to 600 nm. Agglomerates refer to secondary particles that are aggregated by two or more primary particles and present an agglomerated state. The first active material is in the form of highly agglomerated agglomerates. Generally speaking, due to the process of highly agglomerated primary particles, the particle size of the first active material is relatively large. The particle size of the second active material is relatively small, and it is a nano-scale particle. The second active material may be a non-agglomerated primary particle, or a secondary particle with a very low degree of agglomeration (two or three primary particles aggregated). By using a scanning electron microscope (SEM) image, the agglomerated or non-agglomerated state of the particles and the number of agglomerated particles can be observed. Combined with the particle size observed by SEM, the first active material and the second active material in the positive electrode active material layer can be distinguished.

[0043] In the present invention, the manganese content (m%) in the first active material is relatively high, and the manganese content (n%) in the second active material is relatively low or zero. A high-manganese large-particle agglomerate is compounded with low-manganese or manganese-free nano-particles, and a second active material with a smaller particle size is used to fill the inter-particle gaps formed by the large-particle first active material to increase the compaction density; a certain amount of agglomerates are used as positive electrode active materials to reduce the amount of binder used, increase the coating amount per unit area, and increase the surface density; the first active material is a LMFP agglomerate including a high manganese content, and the energy density of the battery is further improved by using a positive electrode active material with a high manganese content. By increasing the compaction density and surface density, as well as a specific manganese content, the battery can achieve a higher energy density. In addition, by compounding low-manganese or manganese-free nano-particles, the fast charging performance is greatly improved while maintaining the high energy density of the battery.

[0044] The difference between m and n should be within an appropriate range, and the difference in manganese content between the two active materials should not be too large or too small. When 0≤mn<15, the difference between the two is too small, which means that the manganese content of the first active material and the second active material is very close, and the high energy density and excellent fast charging performance brought by the combination of high manganese and low manganese cannot be achieved, and it is difficult to reflect the improvement effect of the combination of high and low manganese content materials; when mn>85, the difference between the two is too large, which means that the manganese content in the first active material is too high. Even if the second active material is mixed, the improvement of the ion transmission rate inside the positive electrode active material is relatively limited, resulting in a decrease in the fast charging performance of the battery. When the manganese content in the first active material is lower than the manganese content in the second active material, that is, m<n, the second active material has a high manganese content. Since its particle size is only nanometers, it is very easy to cause manganese dissolution and electrolyte side reactions, resulting in deterioration of battery performance; and although the first active material has a low manganese content, the particle size of the particles is too large and the degree of agglomeration is too high, which also leads to the inability to effectively improve the fast charging performance of the battery.

[0045] Illustratively, in the present invention, the value of mn may be 15, 20, 30, 50, 60, 70, 75, 80, 85, or an interval formed by any two of the above values.

[0046] In one preferred implementation manner, the m and n satisfy the following relationship: 40≤mn≤70.

[0047] When the difference of mn is within the above preferred range, the energy density and fast charging performance of the battery containing the positive electrode plate are better overall.

[0048] In one embodiment, the m and n satisfy the following relationship: 0.10≤n / m≤0.85.

[0049] Illustratively, in the present invention, the value of n / m may be 0.10, 0.15, 0.20, 0.30, 0.50, 0.70, 0.75, 0.80, 0.85, or an interval formed by any two of the above values.

[0050] The difference between m and n (mn) reflects the absolute difference in manganese content in the first and second active materials; unlike the difference, the ratio of n to m (n / m) reflects the relative size relationship between the manganese content in the second active material and the first active material. The present invention has found that when m and n satisfy the difference within the specified range of the present invention, and further satisfy 0.10≤n / m≤0.85, the energy density and fast charging performance of the positive electrode sheet are relatively more balanced.

[0051] In one preferred embodiment, m and n satisfy the following relationship: 0.18≤n / m≤0.45.

[0052] In one embodiment, the m% is 70-95%. For example, the m% can be 70%, 75%, 80%, 85%, 90%, or 95%.

[0053] In one preferred embodiment, the m% is 75-85%.

[0054] Although LMFP with a higher manganese content has a higher specific capacity, as the manganese content increases, the battery's kinetic performance further decreases, and the fast charging performance is poor. When the manganese content is too high, such as exceeding 95%, it is easy to promote the Jahn-Teller effect, resulting in material lattice distortion. Manganese dissolution and reaction with the electrolyte may cause the material's stability to decrease. Excessive heat is generated during the charge and discharge process, affecting the battery's cycle stability and long cycle life. In particular, after a certain number of cycles, the battery's energy density will decrease.

[0055] In one embodiment, the n% is 0-60%, for example, the n% can be 0%, 10%, 15%, 20%, 30%, 40%, 50%, 55%, 58%, or 60%.

[0056] In one preferred embodiment, the n% is 15-40%.

[0057] The n% of the second active material should not be too low. If it is too low (such as less than 15%), the platform voltage may not be significantly increased, affecting the energy density of the overall material. When n% is greater than 40%, the manganese-iron ratio of the positive electrode active material may be too high, resulting in a decrease in the fast charging performance of the battery; and after a certain number of cycles, the structural stability of the material with a high manganese-iron ratio is relatively low, and the battery energy density will also decrease.

[0058] When m% and n% are within the above range, the high-manganese and low-manganese LMFP materials can work together better to achieve better battery kinetic performance, and the fast charging performance of the battery is greatly improved.

[0059] It should be noted that the second active material includes LMFP and / or LFP. When the second active material is LFP, n% is 0%; when n%>0, the second active material can be LMFP or a mixture of LMFP and LFP.

[0060] The present invention does not limit the detection method of m% and n%, and those skilled in the art can detect the manganese content of the positive electrode active material with a specific particle size according to conventional technical means.

[0061] Exemplarily, m% and n% can be detected by the following method:

[0062] The battery is disassembled to obtain the positive electrode sheet, which is then processed to obtain the positive electrode active material powder, which is tested by scanning electron microscope (SEM) and energy dispersive spectrometer (EDS) to obtain m% and n%.

[0063] In one embodiment, the first active material includes secondary particles formed from primary particles, and the average diameter of the primary particles is 20 to 130 nm.

[0064] In one preferred embodiment, the first active material includes secondary particles formed from primary particles, and the average diameter of the primary particles is 40 to 90 nm.

[0065] In the positive electrode active material of the present invention, the average diameter of the primary particles in the first active material is smaller than the particle size of the second active material. For the high manganese LMFP material, due to the high manganese content, its own lithium ion diffusion coefficient decreases, thereby slowing down the charge and discharge rate. In order to make up for the fast charging performance defects caused by the high manganese content, the present invention studies the use of high manganese primary particles with extremely small particle sizes to form high manganese agglomerates, especially preferably using primary particles with an average diameter of 40 to 90 nm, increasing the contact between particles, and enhancing the internal conductivity of the high manganese agglomerates, which can ensure good fast charging performance of the battery.

[0066] For the agglomerate LMFP, after being coated on the surface of the positive current collector as the positive electrode active material, some agglomerates may become loose during the processing of the positive electrode sheet, resulting in the presence of primary particles with a particle size of 20 to 130 nm in the positive electrode active material layer. It should be noted that primary particles within this particle size range (20 to 130 nm) do not belong to the second active material.

[0067] In one embodiment, the molar ratio of manganese to iron (Mn / Fe) in the positive electrode active material is 1.0 to 4.0. For example, the Mn / Fe may be 1.0, 1.5, 1.8, 2.0, 2.5, 3.0, 3.5, 3.8, or 4.0.

[0068] In one preferred embodiment, the molar ratio of manganese element to iron element in the positive electrode active material is 2.0 to 3.5.

[0069] In one embodiment, the positive electrode sheet satisfies the following relationship: 5≤(a×b) / c≤60;

[0070] Said a is the value of mn;

[0071] b is the molar ratio of manganese to iron in the positive electrode active material;

[0072] The c is the peak intensity ratio of the diffraction peaks of the (101) crystal plane and the (020) crystal plane in the XRD spectrum of the positive electrode (denoted as I 101 / I 020 ).

[0073] The positive electrode was tested by XRD. In the XRD spectrum, the diffraction peak at 2θ = 20.7° ± 0.5° (peak intensity is recorded as I 101 ) corresponds to the (101) crystal plane of the positive electrode active material, and the diffraction peak at 2θ = 29.5° ± 0.5° (peak intensity is recorded as I 020 ) corresponds to the (020) crystal plane of the positive electrode active material.

[0074] In the positive electrode active material of the present invention, lithium manganese iron phosphate and lithium iron phosphate are both olivine-type materials. For olivine-type materials, I 020 The (020) crystal plane corresponding to the diffraction peak extends along the b-axis of the crystal. The diffusion of lithium ions in the b-axis direction is the main path during the battery charging and discharging process, so the good development of the (020) crystal plane is an important factor in improving the fast charging performance of the material. However, the rapid deintercalation of lithium ions may cause a sudden change in the lattice, and the change in the lattice structure may cause a decrease in the energy density of the positive electrode. The present invention found that I 101 The (101) crystal plane corresponding to the diffraction peak plays an important role in maintaining the integrity of the lattice and inhibiting lattice mutation. The (101) crystal plane is at a certain angle relative to the b-axis and c-axis in the crystal structure. During rapid charge and discharge, the (101) crystal plane can provide a relatively stable structural platform, which helps to relieve the lattice stress caused by the rapid migration of lithium ions. 101 and I 020 The ratio (i.e. I 101 / I 020 ) can reflect the proportion of (101) crystal plane and (020) crystal plane. In the present invention, by controlling I 101 / I 020 During the rapid charging and discharging process, it not only maintains the structural stability of the material, but also ensures a good lithium ion diffusion path, thereby achieving a balance between fast charging and maintaining energy density of the battery.

[0075] I 101 / I 020 The value of is related to the content and distribution of manganese and iron in the positive electrode active material. Therefore, it is necessary to comprehensively define the values ​​of a, b, and c. The present invention has found that when a, b, and c satisfy 5≤a×b×c≤60, the fast charging performance and energy density of the battery are better.

[0076] The present invention does not limit the detection method of the c value, and those skilled in the art can perform XRD detection on the positive electrode sheet according to conventional technical means.

[0077] In one preferred embodiment, the positive electrode plate satisfies the following relationship: 15≤(a×b) / c≤30.

[0078] In one preferred embodiment, the range of c is 0.75 to 1.13.

[0079] In a further preferred embodiment, the range of c is 0.84 to 1.05.

[0080] When the value of c is within the above preferred range, it means that the (101) crystal plane and the (020) crystal plane are relatively more balanced, which helps to improve the fast charging performance and energy density of the battery.

[0081] In the present invention, the preparation method of LMFP and LFP is not limited, and those skilled in the art can prepare LMFP or LFP according to conventional technical means.

[0082] Exemplarily, the preparation method of LMFP may include the following steps:

[0083] A manganese source, an iron source, a phosphorus source and a lithium source are mixed in a certain molar ratio, deionized water is used as a dispersant, and ball milling is performed;

[0084] The wet material after ball milling is spray-dried to obtain a dry mixed powder;

[0085] The dry powder is sintered in an atmosphere with a nitrogen concentration of less than 150 ppm to obtain LMFP agglomerates.

[0086] The LMFP agglomerates obtained in the previous step are crushed, screened and classified to obtain LMFP nanoparticles within a specific particle size range.

[0087] The preparation method of LFP is similar to that of LMFP, except that no manganese source is added.

[0088] The lithium source may include at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, lithium dihydrogen phosphate, lithium citrate or lithium acetate.

[0089] The phosphorus source may include at least one of diammonium hydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate, or lithium phosphate.

[0090] The iron source may include at least one of ferrous oxalate, ferric hydroxide, ferrous hydroxide, ferric phosphate, ferrous phosphate, ferric acetate, ferrous acetate, ferric carbonate, ferrous carbonate, ferrous oxide, ferrous oxide or ferric oxalate.

[0091] The manganese source may include at least one of manganese carbonate, manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, or manganese acetate.

[0092] When preparing LMFP and / or LFP, the carbon source may be mixed with a manganese source (if any), an iron source, a phosphorus source, and a lithium source as required to obtain LMFP and / or LFP containing a carbon coating layer.

[0093] The carbon source may include at least one of glucose, sucrose, polyethylene glycol (PEG), and polyvinyl alcohol.

[0094] When preparing LMFP and / or LFP, a certain amount of doping element source such as vanadium source (vanadium pentoxide), tungsten source (ammonium metatungstate), titanium source (titanium oxide), magnesium source (magnesium carbonate), etc. can be mixed with manganese source (if any), iron source, phosphorus source, lithium source as needed to obtain LMFP and / or LFP containing a certain amount of doping elements.

[0095] Among them, the structural formula of manganese iron lithium particles is: LiMnxFeyMznPO4, wherein x is greater than 0 and less than 1; y is greater than 0 and less than 1; z is greater than or equal to 0 and less than 1; M refers to the doping element, and n refers to the valence of the doping element; satisfying: 2(x+y)+n*z=2.

[0096] Ferromanganese phosphate can be selected to serve as a manganese source, an iron source and a phosphorus source at the same time; ferric phosphate can be selected to serve as an iron source and a phosphorus source at the same time.

[0097] Optionally, the solvent may be at least one of water and ethanol.

[0098] Optionally, the ball mill can use zirconium oxide as ball milling beads. The diameter of the ball milling beads can be a conventional size in ball milling, such as 0.05-50 mm in diameter. In the ball milling, the mass ratio of the abrasive to the ball milling beads (ball to material ratio) can be adjusted as needed, such as the ball to material ratio can be selected to be (2-10): 1. The conditions of the ball milling can be: time 2-20 hours, rotation speed 200-500 rpm.

[0099] Optionally, the sintering condition may be to heat the material from room temperature to 600-1200° C. at a heating rate of 5-20° C. / min for 5-20 h.

[0100] Optionally, the sintering may also adopt gradient sintering conditions.

[0101] By adjusting the addition amount of manganese source and iron source, the proportion of manganese content in LMFP can be controlled; by adjusting the sintering conditions, crushing and screening and grading conditions, the particle size of LMFP and LFP can be controlled.

[0102] The positive electrode active material can be obtained by directly mixing the first active material and the second active material. The mixing mass ratio of the first active material and the second active material can be (40:60) to (99:1).

[0103] The positive electrode active material layer may further include a conductive agent and a binder in addition to the above-mentioned positive electrode active material.

[0104] The conductive agent can be used as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. In the present invention, there is no particular limitation on the type of the conductive agent. Specifically, the conductive agent can be at least one of carbon nanotubes, carbon black or graphene.

[0105] The binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. In the present invention, the binder can be a conventional choice in the battery field. Specifically, the conductive agent can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) or sodium alginate.

[0106] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.

[0107] The positive electrode sheet of the present invention can be prepared according to conventional methods in the art, for example, the positive electrode active material, the conductive agent and the binder are dispersed in a solvent to form a uniform positive electrode slurry, the positive electrode slurry is coated on the positive electrode current collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.

[0108] One embodiment of the present invention provides an electrochemical device, comprising the positive electrode sheet described above.

[0109] In addition to the positive electrode sheet, the electrochemical device also includes a negative electrode sheet, a separator and an electrolyte.

[0110] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material. For the negative electrode active material, the embodiment of the present invention does not specifically limit the type of the negative electrode active material, and can be selected according to actual needs. As an example, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, and silicon-carbon composites.

[0111] The diaphragm is located between the positive electrode sheet and the negative electrode sheet, and is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. The diaphragm can be any material suitable for an electrochemical energy storage device isolation membrane in the art. Specifically, the diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fiber.

[0112] The electrolyte of the present invention can be any electrolyte suitable for electrochemical energy storage devices in the art. The electrolyte includes an electrolyte and a solvent, and the electrolyte can generally include a lithium salt.

[0113] Specifically, the lithium salt includes lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), lithium difluorobis(oxalate)phosphate (LiDFOP) and lithium tetrafluorooxalate)phosphate (LiTFOP). The concentration of the electrolyte in the electrolyte solution may be 0.5 to 5 mol / L.

[0114] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0115] An embodiment of the present invention provides an electrical device, comprising the electrochemical device described above, wherein the electrochemical device serves as a power supply for the electrical device.

[0116] The electrical device refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy or other energy forms, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it may include but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices may be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles may be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0117] The present invention is further described below with reference to specific embodiments.

[0118] Examples 1 to 19 and Comparative Examples 1 to 3

[0119] Examples 1 to 19 and Comparative Examples 1 to 3 respectively provide a lithium ion battery, and the preparation method is as follows:

[0120] (1) Preparation of positive electrode sheet

[0121] (1.1) Preparation of positive electrode active materials

[0122] Preparation of the first active material:

[0123] According to the target chemical formula LiMn m / 100 Fe 1-m / 100 PO 4 (the value of m is shown in Table 2) wherein the molar ratio of each element Li, Mn, Fe, and P is respectively weighed lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and then mixed. The mixed materials are mixed with glucose and ethanol for the first ball milling. The first ball milling uses zirconium oxide with a diameter of 0.6 mm as ball milling beads, the ball-to-material ratio is 5:1, the rotation speed of the first ball milling is 300 rpm, and the time of the first ball milling is shown in Table 1;

[0124] The wet material after grinding is filtered, air-dried for 2 hours, and then spray-dried for 5 hours to obtain a dry powder, i.e., a precursor;

[0125] The dried powder was placed in a tube furnace and sintered in an atmosphere with an oxygen concentration of less than 150 ppm. The sintering conditions are shown in Table 1: heating from room temperature to 850°C at a heating rate of 12°C / min and maintaining for 960 min; cooling to room temperature;

[0126] The sintered product is graded and screened, and the LMFP agglomerates with a particle size ranging from 4 to 20 μm are selected as the first active material;

[0127] Preparation of the second active material:

[0128] According to the target chemical formula LiMn n / 100Fe 1-n / 100 PO 4 (the value of n is shown in Table 2) wherein the molar ratio of each element Li, Mn, Fe, and P is respectively weighed and mixed with lithium carbonate, manganese carbonate, ferrous oxalate, and diammonium hydrogen phosphate, and the mixed materials are mixed with glucose and ethanol for a second ball milling. The second ball milling uses zirconium oxide with a diameter of 0.6 mm as ball milling beads, the ball-to-material ratio is 5:1, the rotation speed of the second ball milling is 200 rpm, and the time of the second ball milling is shown in Table 1;

[0129] The ground wet material is filtered, air-dried, and spray-dried under the same conditions as the first active material; then sintered. The sintering conditions are: heating from room temperature to 850°C at a rate of 12°C / min, maintaining for 960 minutes; and cooling to room temperature.

[0130] The sintered product is crushed and then graded and screened to select LMFP nano-sized particles (when n is 0, it is LFP nano-sized particles) with a particle size in the range of 200 to 600 nm, which are the second active material;

[0131] (1.2) The first active material and the second active material are uniformly mixed according to the mass ratio shown in Table 1 to obtain a positive electrode active material;

[0132] The positive electrode active material, conductive agent (SP), and binder (PVDF) were mixed in NMP at a mass ratio of 96:1.5:2.5. Subsequently, the mixed positive electrode slurry was evenly coated on an aluminum foil with a thickness of 15 μm, with a coating surface density of 446 m 2 / g, compacted density 2.4m 3 / g; drying in a vacuum furnace at 100°C to obtain a positive electrode sheet, slitting it into strips, and then rolling it to obtain a positive electrode sheet.

[0133] (2) Preparation of negative electrode sheet

[0134] The negative electrode active material (artificial graphite), conductive agent (CNT), and binder (carboxymethyl cellulose, CMC) are mixed in a mass ratio of 96:1.5:2.5, dispersed in deionized water, and made into negative electrode slurry by a wet process using a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode collector (copper foil), and the negative electrode collector coated with the negative electrode slurry is transferred to a vacuum environment in an oven at 100°C for drying for 12 hours, and then rolled and cut to obtain negative electrode sheets.

[0135] (3) Preparation of electrolyte

[0136] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a weight ratio of 3:7 to obtain an organic solvent, and then fully dried lithium salt LiPF 6The electrolyte solution is dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1.15 mol / L.

[0137] (4) Preparation of diaphragm

[0138] Polyethylene (PE) diaphragm is used.

[0139] (5) Preparation of batteries

[0140] The positive electrode sheets, separators and negative electrode sheets prepared above are stacked (40 positive electrode stacking layers and 41 negative electrode stacking layers) to obtain bare cells without liquid injection; the bare cells are placed in outer packaging foil, and the prepared electrolyte is injected into the dried bare cells. After vacuum packaging, standing, forming, shaping, and sorting, a lithium-ion battery with a cell size of 202 mm in length and 90 mm in width is obtained.

[0141] Table 1

[0142]

[0143]

[0144]

[0145] For each embodiment and comparative example, m% of the first active material, n% of the second active material, average primary particle diameter of the first active material, Mn / Fe of the positive electrode active material, and I 101 / I 020 Carry out testing; the testing methods for the above items are as follows:

[0146] m% of the first active material, n% of the second active material: disassemble the lithium-ion battery to obtain a positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, and dry it at room temperature with a humidity of ≤15% to obtain a sheet sample;

[0147] First stick a layer of conductive glue on the sample holder, stick the electrode sample on the sample holder, and then coat a conductive film. Then observe under a scanning electron microscope (SEM) with a magnification of 5KX. Determine the first active material and the second active material based on the morphology of agglomerates and single particles combined with the particle size. Use EDS testing to analyze the molar content of Mn element in the first active material and the second active material, respectively, to obtain m% and n%.

[0148] Average primary particle diameter of the first active material: As described above, the positive electrode active material powder obtained by disassembling the lithium-ion battery is evenly sprinkled on the conductive glue and directly placed in the SEM. A SEM photo with a magnification of 30KN (30KX) and a clear image is selected, and the particle size distribution of the primary particles in the first active material is measured (400 particles are measured) using the particle size measurement software (Nano Measurer) to obtain the average primary particle diameter.

[0149] Mn / Fe of positive electrode active material:

[0150] As described above, the lithium-ion battery is disassembled to obtain the positive electrode active material powder, 0.5 g of the positive electrode active material powder is accurately weighed, dispersed in 20 ml of water, and 10 ml of nitric acid is added. After mixing evenly, the mixture is heated. After the positive electrode active material powder is dissolved, the material is fixed to 100 ml with water to obtain a test solution;

[0151] The solution to be tested was subjected to ICP test. The ICP test conditions were as follows: the wavelength of the element detection spectrum was selected (Fe wavelength 259.94, 238.204, 239.562nm, Mn wavelength 257.61nm), and appropriate ICP instrument working conditions were set according to the characteristics of the sample and the elements to be detected, including a gas flow rate of 0.5L / min and a power of 1150W;

[0152] The Mn / Fe content of the elements can be measured by ICP, and the Mn / Fe content of the entire positive electrode active material can be calculated.

[0153] I 101 / I 020 : The lithium-ion battery was disassembled to obtain the positive electrode piece, and the positive electrode piece was subjected to XRD test. The XRD conditions were: testing was performed using an X-ray diffractometer; Cu target, Start angle was set to 5°, Stop angle was set to 90°, Sampling W was set to 0.02, Scan speed was 3° / min, acceleration voltage was set to 40KV, and acceleration current was set to 40mA.

[0154] The test results of each embodiment and comparative example are shown in Table 2.

[0155] The SEM images of the positive electrode active materials of Example 1 and Example 19 are shown as follows: Figure 1 , Figure 2 shown. Figure 1 In the " Figure 2 The aggregate shown in the figure is the first active material. Figure 1 ", "Score Figure 3 " Figure 4 The particles shown are the second active material.

[0156] The XRD patterns of the positive electrode sheets of Example 1 and Example 19 are respectively as follows: Figure 3 and Figure 4 shown.

[0157] Table 2

[0158]

[0159]

[0160] The fast charging performance and energy density of lithium-ion batteries are tested as follows:

[0161] (1) Fast charging performance:

[0162] The stacked three-electrode test method takes out the positive and negative electrodes of the lithium-ion battery and soaks them in DMC solvent for more than 72 hours, then dries the electrodes in a vacuum oven, and then assembles the positive and negative electrodes into a stacked three-electrode battery cell, with the copper wire as the reference electrode; the test is carried out using a blue and charging and discharging device;

[0163] At 25℃, charge and discharge for two cycles at 0.33C (upper limit voltage 4.25V, lower limit voltage 2.5V), and take the charging capacity of the second cycle as the standard capacity;

[0164] After charging to 10% SOC at 0.33C, start charging at 4C (this time is recorded as time t1), and perform constant current charging with an upper limit voltage of 4.25V or a negative reference potential ≤ 0mv as the cut-off condition. After reaching the cut-off condition, the current is reduced by 0.2C step until the current drops to 0.05C and the charging is stopped. The time when the charging capacity reaches 80% SOC is recorded as t2.

[0165] The time from t1 to t2 (i.e., the time from 10% SOC to 80% SOC) is the fast charging time, in minutes.

[0166] (2) Volume energy density:

[0167] In a 25℃ constant temperature box, the lithium-ion battery was subjected to a charge and discharge cycle test. The charge and discharge system was as follows: charging to 4.25V at a constant current of 0.33C, then charging at a constant voltage until the current dropped to 0.05C, and then discharging the battery at a constant current of 1C to 2.5V after standing for 5 minutes. This was one cycle. After 10 cycles, the discharge capacity of the lithium-ion battery at the 10th cycle was obtained.

[0168] Measuring the surface area S of the positive electrode active material layer and the total thickness T of the positive electrode active material layer in the prepared positive electrode sheet;

[0169] The reversible capacity per unit area of ​​the positive electrode active material layer after cycling (Ah / cm 2) = discharge capacity of the lithium-ion battery at the 10th cycle / surface area S of the positive electrode active material layer;

[0170] The ratio of the reversible capacity per unit area of ​​the positive electrode active material to the total thickness of the positive electrode active material layer after cycling (C / T) (mAh / cm 3 ) = reversible capacity per unit area of ​​the positive electrode active material layer after cycling C / total thickness T of the positive electrode active material layer.

[0171] The volume energy density of a lithium-ion battery after 10 cycles is measured by the ratio of the reversible capacity per unit area of ​​the positive electrode active material to the total thickness of the positive electrode active material layer.

[0172] The test results are shown in Table 3.

[0173] Table 3

[0174]

[0175]

[0176] According to the test results of the embodiments and comparative examples, it can be seen that the lithium-ion battery using the positive electrode sheet prepared in each embodiment of the present application has excellent fast charging performance and energy density, wherein the fast charging time is ≤25.3min and the volume energy density is ≥398mAh / cm 3 .

[0177] According to Examples 1 to 5, it can be seen that when the average diameter of the primary particles of the first active material is 40 to 90 nm, the fast charging performance and energy density of the battery are better overall; when the average diameter of the primary particles is slightly smaller, although the fast charging performance of the battery is improved, the energy density may be reduced, and the processing process is more difficult; when the average diameter of the primary particles is slightly larger, the battery energy density is higher, but the fast charging time is longer, and the fast charging performance is reduced.

[0178] According to Examples 6 to 8 and Example 13, it can be seen that when the value of m exceeds 75 to 85, n exceeds 15 to 40, or the value of n / m exceeds 0.18 to 0.45, the fast charging performance and energy density of the battery cannot be well balanced, and the overall performance of the battery is slightly poor.

[0179] According to Examples 9 to 12, it can be seen that when the positive electrode sheet further satisfies the Mn / Fe ratio of the positive electrode active material of 2.0 to 3.5, I 101 / I 020 When (a / b)*c is 0.84-1.05 and (a / b)*c is 15-30, the fast charging performance and energy density of the battery are relatively better.

[0180] From Example 19, when the second active material is LFP, as long as mn is within the scope of the technical solution of the present invention, good fast charging performance and high energy density of the lithium-ion battery can be achieved.

[0181] According to Comparative Examples 1 to 2, it can be seen that when the value of mn is too large, the manganese content of the first active material and the second active material is difficult to effectively match, resulting in serious degradation of the fast charging performance of the battery. According to Comparative Example 3, when the value of mn is too small, the manganese content of the first active material and the second active material is very close, and the improvement of the fast charging performance and energy density of the battery is not obvious. According to Comparative Example 4, when the manganese content of the second active material is higher than the manganese content of the first active material, the battery performance deteriorates, and the fast charging performance and energy density of the lithium-ion battery are very poor.

[0182] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer contains a positive electrode active material, characterized in that: The positive electrode active material includes a first active material with a particle size of 4 to 20 μm and a second active material with a particle size of 200 to 600 nm; The first active material comprises lithium manganese iron phosphate, and the molar percentage of manganese in the first active material is m%, calculated based on the total molar number of metal elements other than lithium in the first active material, and the m% is 70-95%; The second active material comprises lithium manganese iron phosphate and / or lithium iron phosphate, and the molar percentage of manganese in the second active material is n% based on the total molar number of metal elements other than lithium in the second active material; The positive electrode sheet satisfies the following relationship: 5≤(a×b) / c≤60; Said a is the value of mn; b is the molar ratio of manganese to iron in the positive electrode active material; The c is the peak intensity ratio of the diffraction peaks of the (101) crystal plane and the (020) crystal plane in the XRD spectrum of the positive electrode plate.

2. The positive electrode sheet according to claim 1, characterized in that: The positive electrode plate satisfies the following relationship: 15≤(a×b) / c≤30.

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The range of c is 0.75 to 1.

13.

4. The positive electrode sheet according to claim 1 or 2, characterized in that: The m and the n satisfy the following relationship: 15≤mn≤85.

5. The positive electrode sheet according to claim 4, characterized in that: The m and the n satisfy the following relationship: 40≤mn≤70.

6. The positive electrode sheet according to claim 1 or 2, characterized in that: The m and the n satisfy the following relationship: 0.10≤n / m≤0.

85.

7. The positive electrode sheet according to claim 6, characterized in that: The m and the n satisfy the following relationship: 0.18≤n / m≤0.

45.

8. The positive electrode sheet according to claim 1 or 2, characterized in that: The n% is 0 to 60%.

9. The positive electrode sheet according to claim 1 or 2, characterized in that: The first active material includes secondary particles formed of primary particles, and the average diameter of the primary particles is 20 to 130 nm.

10. The positive electrode sheet according to claim 1 or 2, characterized in that: The molar ratio of manganese element to iron element in the positive electrode active material is 1-4.

11. An electrochemical device, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to any one of claims 1 to 10.

12. An electrical device, characterized in that: An electrochemical device comprising the electrochemical device according to claim 11.

Citation Information

Patent Citations

  • Lithium iron manganese phosphate compound, preparing method thereof, and lithium ion battery positive electrode

    CN112436120A

  • Positive electrode active material, electrochemical device, and electronic apparatus

    CN114400322A

  • Preparation method and application of lithium manganese iron phosphate

    CN115231541A

  • Secondary battery and electric device

    CN115458707A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN116692812A

Cited By

  • Positive electrode sheet, and electrochemical device and electric device comprising same

    WO2026060941A1